Investigation of Heat and Drag Reduction Induced by Forward-Facing Cavity in Hypersonic Flow - Ning Ding; Jianlong Chang; Junhui Liu (Aerospace)
The design of heat and drag reduction systems for hypersonic vehicles has garnered widespread global attention. In this study, the Navier–Stokes equations and the SST k-ω turbulence model are employed to establish a simulation model for heat and drag reduction induced by a forward-facing cavity. The numerical methods are validated using existing experimental results. The oscillation characteristics of the bow shock wave at the head and the shock inside the cavity in hypersonic flows are investigated. The heat and drag reduction mechanisms of the forward-facing cavity are discussed. The effects of the diameter and depth of the cavity on drag and heat reduction are comprehensively analyzed. The obtained results show that a reduction in drag and heat is achieved when a forward-facing cavity is added to the vehicle. The main reasons for this heat reduction are the cold ring mechanism and the energy conversion mechanism. The size of the cold ring is significantly affected by the cavity diameter, whereas the energy conversion mechanism is more sensitive to variations in diameter. The maximum reduction in heat load is 2.2%, and the maximum reduction in the Stanton number is 25.3%. Increases in both diameter and depth enhance drag reduction, achieving an average drag reduction of approximately 1.65%.